Pediatric Anterior Mediastinal Mass: A Review Article. (September 2015) - Pearson, Jared Kevin; Tan, Gee Mei
One of the more challenging cases facing a pediatric anesthesiologist is the management of patients presenting with an anterior mediastinal mass (AMM). Patients with an AMM may have severe cardiopulmonary compromise that can be exacerbated when undergoing general anesthesia. Several case reports have documented cardiopulmonary collapse during induction or maintenance of general anesthesia and even for procedures done without anesthesia. Despite increased understanding and management of these patients, perioperative complications, defined as anything from transient decreases in blood pressure correcting with fluids or mild airway obstruction requiring no intervention, to complete cardiopulmonary collapse, are still estimated to occur during 9% to 20% of anesthetic procedures. The purpose of this review article is to provide foundational knowledge of the anatomy and physiology of a patient with an AMM, with particular emphasis on the pediatric patient. It will assist in recognizing presenting signs and symptoms and discuss the appropriate preoperative testing, which together can help assess perioperative risk and determine the appropriate anesthetic management plan for the patient's safety and comfort.